Instant Messaging (IM) used in the Workplace - Aripin, Norizah; Mustafa, Hasrina; Hussein, Adnan (Journal of Techno-Social, 2011)
Developments in information communication technologies (ICT) is growing rapidly and organizations use the ICT for business tasks. Group organization consists of various levels of management receive technology development to ensure the management and administration to be more effective and efficient. Organizations now have the equipment of modern technology which allows the task is done by using electronic devices to ensure increased productivity among lower, higher and professional management. Computer mediated communication, such as Instant Messaging (IM) used in the workplace other than the use of e-mail. This study discusses the frequency and patterns of use of IM in the workplace. Quantitative methods of survey questionnaires and qualitative methods of conversation analysis used in this study. For survey questionnaire, 379 organizations status MSC involved as respondents. Meanwhile, the conversation analysis approach, using five examples of IM conversations from five different organizations for sample analysis. Data was then analyzed using descriptive (survey questionnaire) and thematic analysis (analysis of IM conversations) to identify the specific themes on IM usage motive at work. The study found that 279 respondents have used IM in organization. Motives intended use of IM to provide work orders, obtain information, maintain relationship together and express feelings.